Local women, global science : fighting AIDS in Kenya - Booth, Karen M., 1962- (Indiana University Press, 2004)
Karen Booth looks closely at the operation of two clinics in Nairobi, & explores how internationally funded & nationally sanctioned interventions to stop the spread of HIV are focused on the working class & poor - those least able to challenge traditional patterns of behavior, including male dominance.